Unveiling the Haveli of Maharaja Ranjit Singh: A Historical and Architectural Analysis of Gujranwala's Heritage (Al-Qamar, 2025)
The Haveli of Maharaja Ranjit Singh in Gujranwala stands as a notable monument, revered as the birthplace of Ranjit Singh. The structure displays architectural influences from both Mughal and Rajput styles, particularly evident in its domes, kiosks, and arches. Currently, the haveli is in a state of severe deterioration, requiring urgent restoration. To transform it into an appealing tourist destination, enhancements such as paintings or mosaics depicting the life of Maharaja Ranjit Singh are suggested to be applied on the panels, columns, and blind arches. Moreover, the presentation of the integrating geometrical motifs and illustrations from the Sikh Manuscripts, especially those pertaining to the Maharaja, into the haveli’s grand hall, are also recommended. Despite its inconspicuous location in a narrow street, the haveli's visibility can be improved through directional signage detailing Ranjit Singh's life and achievements. The adjacent bazaars offer opportunities for the tourists to purchase local souvenirs while immersing themselves in Gujranwala's architectural heritage. The qualitative research methodology is adopted for this paper by employing both primary and secondary resources such as photographs, books, journals, interviews, site visits, and literature reviews. The objectives of this paper are to record the historical background, architectural features, current condition, thus insists and aim at providing the ideas for the restoration and ornamentation of the haveli in order to preserve the rich heritage while simultaneously elevating its allure to the tourists.
Keywords: Haveli; Ranjit Singh; Architecture; Gujranwala’s heritage